PCNA ubiquitination is important, but not essential for translesion DNA synthesis in mammalian cells. - Ayal Hendel; Peter H L Krijger; Noam Diamant; Zohar Goren; Petra Langerak; Jungmin Kim; Thomas Reissner; Kyoo-young Lee; Nicholas E Geacintov; Thomas Carell; Kyungjae Myung; Satoshi Tateishi; et al. (PLoS Genetics, 2011)
Translesion DNA synthesis (TLS) is a DNA damage tolerance mechanism in which specialized low-fidelity DNA polymerases bypass replication-blocking lesions, and it is usually associated with mutagenesis. In Saccharomyces cerevisiae a key event in TLS is the monoubiquitination of PCNA, which enables recruitment of the specialized polymerases to the damaged site through their ubiquitin-binding domain. In mammals, however, there is a debate on the requirement for ubiquitinated PCNA (PCNA-Ub) in TLS. We show that UV-induced Rpa foci, indicative of single-stranded DNA (ssDNA) regions caused by UV, accumulate faster and disappear more slowly in Pcna(K164R/K164R) cells, which are resistant to PCNA ubiquitination, compared to Pcna(+/+) cells, consistent with a TLS defect. Direct analysis of TLS in these cells, using gapped plasmids with site-specific lesions, showed that TLS is strongly reduced across UV lesions and the cisplatin-induced intrastrand GG crosslink. A similar effect was obtained in cells lacking Rad18, the E3 ubiquitin ligase which monoubiquitinates PCNA. Consistently, cells lacking Usp1, the enzyme that de-ubiquitinates PCNA exhibited increased TLS across a UV lesion and the cisplatin adduct. In contrast, cells lacking the Rad5-homologs Shprh and Hltf, which polyubiquitinate PCNA, exhibited normal TLS. Knocking down the expression of the TLS genes Rev3L, PolH, or Rev1 in Pcna(K164R/K164R) mouse embryo fibroblasts caused each an increased sensitivity to UV radiation, indicating the existence of TLS pathways that are independent of PCNA-Ub. Taken together these results indicate that PCNA-Ub is required for maximal TLS. However, TLS polymerases can be recruited to damaged DNA also in the absence of PCNA-Ub, and perform TLS, albeit at a significantly lower efficiency and altered mutagenic specificity.